Draw your story: Exploring adaptation experiences of first-year students at the institute of teacher education in Malaysia - Tengku Norhani Tengku Besar; Nor Shafrin Ahmad; Shahabuddin Hashim; Siti Salina Abdullah (Institute of Advanced Engineering and Science, 2021)
The transition from school to the institute of higher learning is a challenging phase that requires students to adapt to new environments and cultures. This study aimed to explore the adaptation experiences of first-year students at the Institute of Teacher Education by using storytelling through drawing. This study involved 18 students pursuing the Bachelor of Education Preparatory Programme at the Institute of Teacher Education in Malaysia with low levels of adaptation identified through Student Adaptation to College Questionnaire (SACQ). The qualitative data were analyzed using thematic analysis. Findings showed that the first-year students at the Institute of Teacher Education experiencing adaptation challenge in four main themes: academic, social, personal, and interest. The findings of this study are expected to contribute towards the formation and development of appropriate interventions to assist the well-being of first-year students at the Institute of Teacher Education, Malaysia, in adapting to the new environment.